Análise multitemporal do uso e cobertura das terras no município de Iraquara, Bahia, no período de 2009 a 2016 - Martins, Elaine de Oliveira (2018)
Water is an essential natural resource for the survival of living beings, a high value is used in the development of economic activities and human dependence on water resources becomes increasingly evident. These already show signs of scarcity in some regions of planet Earth, either through indiscriminate use or poor distribution, as is the case of the Northeastern semi-arid, where the municipality of this study is located. Iraquara is located in the Center-North portion of the State of Bahia, located on an extensive area of carbonate rocks, which is an important karst aquifer. The soil type and the topography of the municipality favor agriculture, the main economic activity. However, the inherent characteristics of a karst environment in semi-arid climate, the low surface courses, have hampered the development of this agricultural activity, which in recent years has been replaced by irrigation techniques that exploit groundwater from the drilling of tubular wells as a means of irrigating cultivated areas. Based on this, this work has as main objective to analyze the changes in land use and coverage in the municipality of Iraquara-Ba, through geotechnologies, from 2009 to 2016. The multitemporal analysis included images from the Landsat-5 TM satellite , and Landsat-8 OLI, to achieve the objectives, we used methodological procedures that guided this research, such as: theoretical base construction, vector and raster data acquisition, tubular wells mapping, Digital Image Processing (PDI) which generated the Land Use and Coverage maps for the year 2009 and 2016 by means of the Bhattacharyya interpolator algorithm, the fieldwork was carried out to validate the maps and to subsidize the calculation of the Tau, Global Accuracy and Commission and Omission, we applied the cross tabulation between land use and land cover, the years of study, which generated a transition matrix and the intersection of the classes to generate the map of muda child. The results of this research showed that the number of wells drilled in the municipality is increasing, the period between 2010-2016 stands out with the number of 112 drilled wells, representing 83% of the wells mapped in the field, with the highest concentration being found on the karst relief, and present higher flows. There were modifications in the classes of uses studied, with significant advance of the class irrigated agriculture and consequent reduction of the agricultural use class / exposed soil.